Magnetic, thermal, mesomorphic and thermoelectric properties of mononuclear, dimeric and polymeric iron(II) complexes with conjugated ligands - Abdullah, Norbani; Elsheikh, Mohamed Hamid; Ibrahim, Nik Muhd Jazli Nik; Said, Suhana Mohd; Sabri, Mohd Faizul Mohd; Masjuki, Haji Hassan; Marlina, Anita (Royal Society of Chemistry, 2015)
Three iron(II) complexes with conjugated multidonor ligands (L1 and L2) studied as thermally stable magnetic and thermoelectric materials were Fe-2(CH3COO)(4)(L1)(2) (1), Fe(L1)(3)(BF4)(2)center dot 4H(2)O (2), and {Fe-2(CH3COO)(4)(L2)center dot 2H(2)O}(n) (3). These complexes have low optical band gaps (1.9 eV for 1 and 2, and 2.2 eV for 3) and were magnetic with 57% high-spin Fe(II) in 1, 33% in 2, and 100% in 3 at 25 degrees C. Complex 1 melted at 57.2 degrees C and exhibited mesomorphism, while 2 melted at 96.9 degrees C, defining it as an ionic liquid. The thermal stabilities of 1 (T-dec = 199 degrees C) and 3 (T-dec = 191 degrees C) were lower than 2 (T-dec = 248 degrees C). Their Seebeck coefficients, S-e (in mV K-1) were -0.65 for 1, -0.54 for 2, and +0.25 for 3, identifying them as potential thermoelectric materials. Complex 1 formed stable thin films on quartz by the spin coating technique. The films formed at aging time t = 0 (F1) and t = 7 days (F2) were made up of monomers of 1. The optical band gaps of the films (1.39 eV for F1 and 1.57 eV for F2) were lower than 1. The films were free of cracks and have a fairly homogeneous morphology. The films with the best morphology were F1 annealed at 40 degrees C and F2 annealed at 60 degrees C.